Nanoparticles: biosynthesis, translocation and role in plant metabolism. Issue 4 (17th April 2019) - Faraz, Ahmad; Faizan, Mohammad; Sami, Fareen; Siddiqui, Husna; Pichtel, John; Hayat, Shamsul
Abstract : Nanotechnology is an emerging field of science that applies particles between 1 and 100 nm in size for a range of practical uses. Nano‐technological discoveries have opened novel applications in biotechnology and agriculture. Many reactions involving nanoparticles (NPs) are more efficient compared to those of their respective bulk materials. NPs obtained from plant material, denoted as biogenic or phytosynthesised NPs, are preferred over chemically synthesised NPs due to their low toxicity, rapid reactions and cost‐effective production. NPs impart both positive and negative impacts on plant growth and development. NPs exhibit their unique actions as a function of their size, reactivity, surface area and concentration. An insight into NP biosynthesis and translocation within the plant system will shed some light on the roles and mechanisms of NP‐mediated regulation of plant metabolism. This review is a step towards that goal.